Phishing Web Sites Features Classification Based on Extreme Learning Machine - Sonmez, Yasin; Tuncer, Turker; Gokal, Huseyin; Avci, Engin (Ieee, 2018)
Phishing are one of the most common and most dangerous attacks among cybercrimes. The aim of these attacks is to steal the information used by individuals and organizations to conduct transactions. Phishing websites contain various hints among their contents and web browser-based information. The purpose of this study is to perform Extreme Learning Machine (ELM) based classification for 30 features including Phishing Websites Data in UC Irvine Machine Learning Repository database. For results assessment, ELM was compared with other machine learning methods such as Support Vector Machine (SVM), Naive Bayes (NB) and detected to have the highest accuracy of 95.34%
6th International Symposium on Digital Forensic and Security (ISDFS) -- MAR 22-25, 2018 -- Antalya, TURKEY
Keywords: Extreme Learning Machine; Features Classification; Information Security; Phishing